RESISTING AND RE-APPROPRIATING ENGLISH IN PESANTREN: Islamic Identity As A Compass - Muhammad Jauhari Sofi; Muhlisin Muhlisin; Dewi Puspitasari (UIN Sumatera Utara, 2026)
English learning in Indonesia is often framed as a neutral response to globalization, yet its ideological dimensions become especially visible in religious educational contexts. Drawing on a postcolonial and critical applied linguistics lens, this study examines how English learning in pesantren has been represented in existing EFL research with particular attention to student resistance and re-appropriation. Adopting a narrative review approach, the study synthesizes 28 scholarly sources comprising peer-reviewed journal articles, conference proceedings, and book chapters on EFL practices in pesantren. The findings show that resistance to English is shaped by ideological, curricular, interactional, and structural factors; it signals efforts to govern the language’s moral and cultural significance rather than a simple rejection of language learning. At the same time, English is actively re-appropriated through the localization of teaching materials, its use for Islamic purposes such as da‘wah, and hybrid multilingual strategies involving English, Arabic, and Indonesian. These processes accentuate forms of learner and teacher agency and challenge Western-centered models of English education. The study further emphasizes the need for context-sensitive pedagogies and highlights pesantren as an important site of postcolonial linguistic negotiation and epistemic agency.